Antiviral, cyototoxic and antimicrobial activities of anthraquinones isolated from the roots of Morinda elliptica - Ali, Abdul Manaf; Ismail, Nor Hadiani; Mohamed Mackeen, Muhammad Mukram; Saiful Yazan, Latifah; Mohamed, S. M.; Ho, A. S. H.; Lajis, Nordin (Taylor & Francis, 2000)
2-Formyl-1-hydroxyanthraquinone, along with ten other known anthraquinones (1-hydroxy-2-methylanthraquinone, nordamnacanthal, damnacanthal, lucidin-?-methyl ether, rubiadin, rubiadin-1-methyl ether, soranjidiol, morindone, morindone-5-methyl ether and alizarin-1-methyl ether), isolated from the roots of Morinda elliptica , were assayed for anti-HIV, cytotoxic and antimicrobial activites. Only damnacanthal showed moderate activity against HIV. It was cytotoxic towards the MCF-7 (breast carcinoma) and CEM-SS (T-lymphoblastic leukaemia) cell line. Nordamnacanthal was very cytotoxic against the CEM-SS cell lines. Other anthraquinones that showed strong cytotoxicity towards the cell lines tested were lucidin-?-methyl ether (CEM-SS and MCF-7) and rubiadin (CEM-SS). Three anthraquinones viz., nordamnacanthal, damnacanthal and morindone, were found to have strong antimicrobial activity.